Teaching Mathematics with Love: Towards an Emotionally Meaningful Pedagogy - Rodríguez Salazar, Ingrid Daniela (2026)
This essay proposes a critical reflection on the teaching of mathematics from the affective dimension, questioning the technocratic approaches that have made students’ emotional experiences invisible. The main objective is to argue for the necessity of a humanized pedagogy that articulates the affective dimension with disciplinary rigor, based on a literature review of key sources on the affective domain in mathematics education and social-emotional learning. The methodology is based on a theoretical-reflective approach, analyzing the premises of the affective domain theory and its articulation with the processes of teaching and learning mathematics. Among the main findings, it is highlighted that emotional pedagogy not only improves the student’s relationship with the discipline but also promotes self-efficacy, resilience, and critical thinking. Finally, it is concluded that the implementation of an affective approach in the mathematics classroom, focused on developing the empathy and emotional intelligence of the teaching staff, is a pathway to transform pedagogical practice and generate meaningful and lasting learning.